IMPLIKASI ASEAN TOURISM STRATEGIC PLAN (ATSP) 2016-2025 DALAM PENGEMBANGAN PROJECT TEN NEW BALI’S INDONESIA - Dini Septyana Rahayu; Dewi Sulistyawati (Dauliyah Journal of Islamic and International Affairs, 2021)
Indonesia as one of the ASEAN member countries that has the largest tourism potential in Southeast Asia requires a special strategy in order to increase Indonesia’s competitiveness in the international sphere. Meanwhile, ASEAN in order to increase tourism potential in the Southeast Asian region has agreed on an ATSP (ASEAN Tourism Strategic Plan) policy framework for two periods, I and II. This policy has implications for policy-making related to tourism in ASEAN member countries, including Indonesia. This study aims to discuss the ATSP (ASEAN Tourism Strategic Plan) II 2016-2025 on Indonesia’s tourism policy. ATSP II 2016-2025 is a form of tourism regime in Southeast Asia that in uences the formulation of Indonesia’s tourism strategy, the Ten New Bali Project. The development of the Ten New Bali Project includes Lake Toba North Sumatra, Tanjung Lesung Banten, the Thousand Islands Jakarta, Tanjung Kelayang Beach Bangka Belitung, Borobudur Temple in Central Java, Mount Bromo in East Java, Mandalika West Nusa Tenggara, Labuan Bajo East Nusa Tenggara, Wakatobi South Sulawesi and Morotai Island, North Maluku. This study uses the concept of an international regime and sustainable tourism, to explain the linkage of tourism and tourism strategies in the Southeast Asian region which encourages Indonesia to formulate strategies to increase national competitiveness. This study uses a qualitative method with data collection techniques documentation and interviews. Data documentation is taken from a number of official documents, namely ASEAN, the Ministry of Tourism & Creative Economy of the Republic of Indonesia, scientific journals, scientific articles, newspapers, and interviews.